NURSING CARE AND FAMILY CARE FOR CHILDREN WITH SPECIAL HEALTH NEEDS: INTEGRATIVE LITERATURE REVIEW - Inácio, Ana Luiza Rodrigues; Peixoto, Ana Paula Gomes Lima (Journal of Health Care, 2017)
Introduction: Children with special health care needs continuously demand services that provide support beyond those required by children in general. Objectives: Describing the nursing and family care provided to children with special health needs. Materials and method: Integrative literature revision in the Virtual Health Library database (BVS-Bireme), considering the descriptors "children with disabilities", "nursing care" and "caregivers". Only articles about the selected theme were included, which were published in Portuguese, during the period from January 2000 to December 2015, available online, in full and free. Results: There is still a great lack of preparation of the families to continue the treatment of children with special needs at home. As a justification, we can point a distance between the health staff and the patient's family, a scenario in which the family nucleus has not been assisted as a whole, since the staff focuses its attention only on biomedical care. Furthermore, there is so many special cares, which requires more preparation and qualification for the nursing related to the demands for care of the child and its family. Conclusion: When studying the professional health care and the family context, with their various aspects of care, it is recognized the need to seek theoretical growth and training in the area, such as the comprehensive concepts to deal with the child with special needs that respect its complexity and subjectivity for a high-quality care.
Keywords: Children with disabilities; nursing care; caregivers.